A Comparative Study on Effects of Emotion-Focused Therapy and Self-Perception Training on Autonomous Academic Motivation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to compare the effects of emotion-focused therapy (EFT) and self-perception training (SPT) on autonomous academic motivation (AAM). The extant study was applied research in terms of objective. This also was an experimental research with a pretest-posttest plan and control group (multiple groups). The sampling process was conducted based on a cluster multistage method in which one education district (among two studied districts) was selected randomly. There were four schools among the girls' high schools situated in the selected district. Two classes were chosen from each selected school and 30 subjects were randomly chosen from each class. The total population equaled 240 (N=240). The studied sample comprised 75 subjects (n=75); of which, 25 subjects were assigned to two therapy groups (self-perception training and EFT), as well as one control group. The autonomous Motivation Scale (AMS) designed by Vallerand, Blais, Brière, and Senécal (1992) was employed to assess the autonomous motivation of students. Multivariate Analysis of Covariance (MANCOVA) was used to examine the effectiveness of considered interventions. Moreover, the One-Sample Kolmogorov-Smirnov Test was used to follow statistical presumptions of MANCOVA, and Levin, Box tests were used to testing normality presumption. Tukey test was also employed to compare effectiveness levels of studied interventions in this research. The obtained results indicated higher effectiveness of self-perception training (rather than EFT) on the autonomous academic motivation of female high-school students in Ardabil, Iran.